Interactive Effects of Tetracyclines and Copper on Plant Growth and Nutrient Uptake by Eichhornia crassipes. Issue 1 (13th November 2015) - Lu, Xin; Gao, Yan; Luo, Jia; Yan, Shaohua; Wang, Tong; Liu, Lizhu; Zhang, Zhenhua
Abstract : A hydroponic experiment was conducted to investigate the growth and nutrient uptake by water hyacinth ( Eichhornia crassipes ) under the combined stress of typical veterinary antibiotic tetracyclines (TCs) with copper (Cu). Although E. crassipes proved relatively high tolerance to the co‐contamination of Cu and TCs, the plant growth and nutrient uptake were significantly and interactively influenced by co‐contamination between Cu and TCs after 20 days of growth. The inhibitory effects of Cu or TCs were more evident on physiological parameters than morphological parameters. An increase in the concentrations of Cu or TCs in solution was associated with a greater decrease in plant growth and nutrient uptake. The growth of shoots and nitrogen (N) and phosphorus (P) uptake by shoots were less affected by Cu/TCs compared to roots. The inhibitory effect of TCs on plants growth and nutrient uptake was much stronger than that of Cu, but the opposite was true for N and P concentrations in plant tissues. The mixture of TCs with the low‐Cu showed a reduction in plant growth and nutrient uptake compared with the sole treatments of TCs; while the inhibition was alleviated with increases of Cu concentrations in solution. Therefore, the interactive effects of TCs and Cu should be taken into consideration to achieve a better knowledge on phytotoxicity and bioavailability of co‐contamination between antibiotics and heavy metals to aquatic plants. Abstract : The present study investigates the plant growth and nutrient uptake by water hyacinth ( Eichhornia crassipes ) under the combined stress of tetracyclines (TCs) with copper (Cu). The plant growth and nutrient uptake are negatively influenced by the increase of Cu or TCs concentrations, and an interactive effect of TCs and Cu on plant growth and nutrient uptake can be observed.